(untitled) (ENTHYMEMA, 2023)
This article examines Levi’s treatment of eugenics in “I sintetici” and “Procacciatori d’affari” from Vizio di forma. The study builds upon Francesco Cassata’s analysis, which established that Levi held complex and conflicting views on the topic. These views mirrored his strong belief in avoiding limitations on scientific research while also revealing his ethical concerns. To further understand this predicament, the study reads Levi’s stories against the debate on eugenics that took place in England in the 1920s-1930. This debate engaged scientists and writers who significantly influenced Levi beyond this subject, including the Huxley brothers and Bertrand Russell. In this intellectual milieu, science fiction emerged as a favoured genre for exploring the intricate facets of eugenics and its ethical ramifications. By undertaking a comparative analysis between these antecedents and Vizio di forma, this study investigates how and why Levi turned to science fiction to articulate his conflicting thoughts on eugenics.